A WOMAN’S SUBJECTIVITY IN ḤANĪN AL-ṢĀYIGH’S MĪTHĀQ AL-NISĀ’: AN EXISTENTIAL FEMINIST PERSPECTIVE BY SIMONE DE BEAUVOIR - Laili Ni'matun Bahriyyah (Arabic Literature Department, 2026)
Mīthāq al-Nisā’ by Ḥanīn al-Ṣāyigh depicts the existential struggles of a woman in Lebanon’s patriarchal Druze society, in which women’s bodies and fates are governed by religious authorities. The study aims to examine the position of Amal, the main female character, trapped in oppressive immanence, and her transcendental efforts to achieve her subjectivity. This descriptive study employs Simone de Beauvoir’s existential feminism as its approach. The findings reveal two key points. First, a woman exists within immanence as the Other due to the objectification of her body and social confinement. Second, subjectivity emerges through gradual transcendence, namely the bodily negotiation in exchange for education, economic independence, divorce, inter-community marriage, and international migration. Amal successfully transforms from the position of an object (the Other) into an authentic subject who holds full power over her own life. This study is expected to contributes to the development of existential feminism in the field of contemporary Arab literary studies, specifically in the Middle Eastern societal context, and offers a new perspective on women’s subjectivity against communal patriarchal structures.